Analisis Manajemen Dakwah Pondok Pesantren Dalam Menjadikan Kampung Madinah di Desa Temboro (Studi Fenomenologi di Pondok Pesantren Putra Al-Fatah Temboro) - Sri Widyastri (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2022)
This paper aims to analyze how the management of Islamic boarding school da'wah in making a Medina village in Temboro. Putra Al-Fatah Islamic Boarding School Temboro is a salaf Islamic boarding school that also has a plus in the field of da'wah. The Putra Al-Fatah Islamic Boarding School is located in the Temboro village area, Karas district, Magetan district. The da'wah of the students of the Putra Al-Fatah Islamic Boarding School provides changes to the village of Temboro, namely the people of the village of Temboro can practice religion and practice the sunnah of the Prophet Muhammad. So that the results of the da'wah make the atmosphere in the village like the atmosphere of Medina. And many are dubbed as Kampung Medina which is located in East Java. From this success, the authors are interested in knowing the management of da'wah carried out by students of the Al-Fatah Islamic Boarding School.The method used in this research is qualitative and the approach uses phenomenology. That is, the author tries to understand the meaning of an event and the interaction of people in certain situations. As well as data collection through observation, interviews and documentation.The results of the research from the analysis of da'wah management carried out by the Putra Al-Fatah Islamic Boarding School by applying the basic principles of management, namely making good planning, organizing, mobilizing to evaluating program implementation. has three stages. The formulation stage focuses on developing the vision and mission, establishing strengths, goals, and objectives. The second stage is the activity of carrying out da'wah activities, as well as conveying the message of da'wah that has been planned. The third stage is evaluation, namely an assessment of the results of da'wah, as well as reports on the performance of da'wah activities at the Putra Al-Fatah Islamic Boarding School. Keywords: Da'wah Management, Islamic Boarding School, Civil Society